Combining biochar with sediment in the treatment for the effectiveness of sulfate and heavy metal Pb reduction of acid mine drainage - Fahruddin, Fahruddin; Syahri, Yolanda Fitria; Fauziah, St.; Samawi, Muhammad Farid; Johannes, Eva; Tambaru, Elis; Tuwo, Mustika; Abdullah, As’adi (Brawijaya University, 2024)
The increasing mining activities have led to the problem of acid mine drainage (AMD) pollution. A method that combines biochar treatment as an adsorbent with wetland sediment treatment as a source of sulfate-reducing bacteria is used to address AMD effectively. This research aimed to determine the ability of biochar in combination with wetland sediment treatment to reduce sulfate and heavy metal content in acid mine drainage wastewater. This research was conducted on a laboratory scale in an AMD wastewater treatment reactor with the following treatments of biochar mixed with wetland sediment. Observations included sulfate content, pH, and heavy metal content. Scanning electron microscope (SEM) analysis was also performed on the biochar. SEM observations revealed the presence of small, dense, and irregularly shaped pores on the surface of the biochar. The results on day 30 showed that biochar mixed with wetland sediment was able to reduce sulfate concentration by 74.19% and reduced Pb by 73.79%, compared with treatment sediment only to 64.81% sulfate concentration and reduced Pb by 53.85%, treatment biochar only had reduced sulfate of 46.90% and reduced Pb by 58.67% and control 1.79% sulfate concentration and reduced Pb by 1.87%.